1994
DOI: 10.1107/s0108270194003306
|View full text |Cite
|
Sign up to set email alerts
|

1-Diphenylphosphino-2-methyl-1,2-dicarba-closo-dodecaborane(12)

Abstract: Two C atoms from two phenyl groups and one C atom of the 2-methyl-1,2-dicarba-closododecaborane cage in the title compound,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…21 The crystal The π orbital overlap between phenyl group and tangential cluster orbitals has been invoked to explain the cage C-C lengthening in aryl-ortho-carborane derivatives. 24,25 This was further explored by ab initio RHF/6-31G* and MP2/6-31G* calculational studies on 1-phenylortho-carborane and other aryl-carboranes in order to probe the orientational preferences of aryl groups attached to the carbon atoms of ortho-carborane. 26,27 These calculations have indicated that, although the overall energy of an aryl-carborane may vary only slightly with the aryl group orientation, the latter does have a perceptible influence on the C(1)-C(2) bond distance, which is greatest when the aryl group is aligned perpendicular to the aryl C-C(1)-C(2) plane.…”
Section: Structural Aspectsmentioning
confidence: 99%
“…21 The crystal The π orbital overlap between phenyl group and tangential cluster orbitals has been invoked to explain the cage C-C lengthening in aryl-ortho-carborane derivatives. 24,25 This was further explored by ab initio RHF/6-31G* and MP2/6-31G* calculational studies on 1-phenylortho-carborane and other aryl-carboranes in order to probe the orientational preferences of aryl groups attached to the carbon atoms of ortho-carborane. 26,27 These calculations have indicated that, although the overall energy of an aryl-carborane may vary only slightly with the aryl group orientation, the latter does have a perceptible influence on the C(1)-C(2) bond distance, which is greatest when the aryl group is aligned perpendicular to the aryl C-C(1)-C(2) plane.…”
Section: Structural Aspectsmentioning
confidence: 99%
“…[12][13][14][15][16][17] Welch carried out systematic studies of aryl-ortho-carboranes bearing substituents of varied bulk 4 on the second carbon atom, enabling him to document both the steric and subtle electronic effects on the cage C1-C2 distance. 12,13,14,15 Teixidor and Viñas, in extensive studies 16 on thiolato (RSCb o R') and phosphino (R 2 PCb o R') derivatives of orthocarborane, found the cage C1-C2 distances varied in a manner they attributed to steric and electronic factors and, more recently, 17 to exo C-X -bonding effects such as we advocate below.…”
Section: Introductionmentioning
confidence: 99%
“…A perpendicular orientation minimises non-bonding repulsions with the other substituent on C(12), and maximises the opportunity for dative π-bonding from the π-system of the phenyl group to the carborane cage. 16,17 The cage carbon-carbon distance, C(1)-C(2), of ortho carborane is the cage edge link known to be most sensitive to the presence of π-bonding substituents on the cage hypercarbon atoms. 11,18,19 Its length increases as exo π-bonding increases.…”
mentioning
confidence: 99%